Is rifaximin better than nonabsorbable disaccharides in hepatic encephalopathy?: A meta-analysis. Issue 51 (23rd December 2021) - Cheng, Junxiong; Chen, Yafang; Cao, Wenfu; Zuo, Guoqing
Abstract: Background: The purpose of the present meta-analysis was to compare the efficacy of rifaximin and nonabsorbable disaccharides (NADs) in hepatic encephalopathy (HE). Methods: After the registration of the present meta-analysis on INPLASY, all procedures were performed according to PRISMA 2020. Relevant literature was retrieved on PubMed, Embase, and the Cochrane Library up to September 5, 2021. The Newcastle-Ottawa Scale (NOS) was used to assess the quality of the enrolled studies, and Review Manager software (version 5.3) was used to analyze the clinical efficacy, blood ammonia and adverse effects. Results: Six studies with 559 patients were included in the present meta-analysis. There were no significant differences in the basic characteristics of the included studies. Analysis of the complete resolution of HE showed that rifaximin was better than NADs (risk ratio [RR] = 1.87, 95% confidence interval [CI] = 1.03–3.39, P  = .04). However, there were no significant differences in mental status (RR = 1.04, 95% CI = 0.92–1.18, P  = .53), blood ammonia level (standard mean difference = −0.02, 95% CI = −0.40–0.02, P  = .08), or drug adverse drug effects (OR = 0.43, 95% CI = 0.10–1.77, I 2  = 56%, P  = .24) between the rifaximin and NADs treatment groups. Conclusion: Rifaximin is not superior to NADs in the treatment of HE.